A STUDY ON KURDISH STUDENTS' ATTITUDES TO GROUP WORK IN THE EFL CLASSROOM - Othman, Hozan Gorgeen; Murad, Ivan Hasan (European Scientific Journal, ESJ, 2015)
Throughout the last two or three decades, group work has become a part that cannot be separated from other classroom activities. This research study identifies the different opinions of Kurdish students concerning the advantages and disadvantages of group work in the classroom. The research was conducted on 100 Kurdish university students who had at least two years experience of group work at Universities in Kurdistan (Zakho, Dohuk, Salahaddin, and Sulaimani universities). Anonymously, a questionnaire was completed and its results were submitted by the respondents, hoping that their responses could directly address the research aim. Then, 20 students from the ones who participated in filling in the questionnaire were chosen and interviewed so as to gain as valid and reliable data as possible for the results of the study to be authentic. Thus, a triangulation methodological strategy was followed in this research study to produce valid results. The findings from both instruments revealed that â€œbetter communicationâ€, â€œgroup work is a mutual interestâ€, â€œgroup members clarify difficult things to each otherâ€ and ''it takes a short time to finish a task in group work'' were studentsâ€™ positive opinions, while â€œsome members prefer to relax and stay silentâ€, â€œsome members do not like to workâ€, ''group work is a waste of time as students talk about external things and they cannot reach any agreement' 'and â€œstudents depend on each otherâ€ were their negative opinions concerning group work. Suggesting further considerable studies on attitudes of students concerning group work, the research concludes.